Wpływ Zamocowania Przekroju Ukośnego na Naprężenia w Rurze Cienkościennej - Kornecki, A. (Engineering Transactions, 1957)
This paper is devoted to consideration of the state of stress and strain in a thin-walled circularly cylindrical shell subjected to internal pressure and with one oblique section rigidly fixed. Common engineering methods are used to solve the problem which is divided into, (1), determining the stresses and displacements according to the membrane theory, and (2), computing the so-called edge effect. Asymptotic method of integrating differential equations of the theory of thin-walled shells-as developed by A.L.Goldenveiser - is used throughout the paper.